Perbandingan Pendapatan Peternak Ayam Ras Pedaging (Broiler) Antara Sistem Kontrak dan Semi Kontrak di Kabupaten Kampar - Chika Afri Mulya; Cepriadi Cepriadi; Ermi Tety (Journal of Agribusiness and Community Empowerment (JACE), 2021)
The purpose of this study is to determine the income of broiler chicken breeders in contract and semi-contract systems in Kampar Regency and analyze the comparison of broiler chicken breeder income between broiler systems and semi-contract systems in Kampar Regency. Broiler chicken business with a pattern of partnership has spread in entire of Indonesia, one of them is in Riau Province. The largest population of broiler chickens in Riau Province is in Kampar Regency. Commonly, there are two the broiler chicken farms partnership patterns in Kampar District,namely the contract system and and semi- contract system between the broiler farmer and poultry companies or poultry shop. The contract system is a binding agreements between the parties relating to the both of the input production’s price and the arvestings price, while the semi-contract are not bound in term of both of the input production’s price and the arvestings price. The objective of the study is analyzed comparison of broiler chicken farm income between contracts system and semi-contract system. The study conducted in Kampar Districtby using survey method for 40 broiler chicken farmer. The results of study shows that the average net income of the broiler farmer on the contract system is lower than the semi contrct system, which is IDR  13.910.273,61for compared to IDR 21.387.673,94. The semi contract broiler chicken farm business is more efficient (RCR=1.12) compared to the contract system (RCR=1.08).